Characteristics in the Population of Stray Dogs and Changes After One Year From a City in Southern Mexico - A. Novelo-Sanguino; M. Jiménez-Coello; J. C. Segura-Correa; A. Ortega-Pacheco (Veterinary Medicine International)
The present study generated evidence on the population of stray dogs in the city of Mérida Yucatán, Mexico. The sighting method was used using the “count within a selected block” method recommended by the World Society for the Protection of Animals. For the sample size, 21 blocks were randomly selected from the city. The calculation of the density of the dogs was obtained considering the extension of 186.24 km2 of the city, and the characteristics of the dogs were evaluated through direct observation. The same protocol was performed 1 year later. The estimated number of dogs was 4764 ± 478 in 2022 and later increased to 7650 ± 779 in 2023 (p<0.006). The density of the dog population in 2022 was 25.6 ± 2.6 animals/km2, with a dog-human ratio of 0.5:100. In 2023, a population density of 41.1 ± 4.3 animals/km2 and a dog-human ratio of 0.8:100 were obtained. This significant increase may be due to more food availability and capacity to achieve a successful reproduction in the first year of observation. However, bias may be considered when using any counting methodology of stray dogs since their mobility may be intensely variable. The male-female ratio was 2.4:1 for 2022 and 2.3:1 for the year 2023. Most of the dogs were adults, of mixed breed, and with solitary behaviour in both years. The body condition in 2022 was predominantly ideal, with a significant decrease in 2023 (p<0.001) probably because of the increased number and competence for food when the second evaluation was performed. When comparing the population according to the areas of the city, the southern area had a higher proportion of thin dogs in both years, with an increase of up to 30% (p<0.001) by 2023. The presence of dermatological conditions in the dogs increased from 4% in 2022 to 15% in 2023 (p<0.001). It is concluded that the number and characteristics of stray dogs studied presented changes over a year time probably because of the carrying capacity of the environment, with differences between areas of the city, particularly in lower socioeconomical areas.